Karl Brunner's philosophy of science: Macroeconomics through the lens of logical empiricism - Kevin D. Hoover (Duke University, Center for the History of Political Economy (CHOPE), 2018)
Best known as a monetary economist and prominent proponent of monetarism, Karl Brunner was deeply knowledgeable about the philosophy of science and attempted to explicitly integrate logical empiricist thinking, derived in some measure from his engagement with the work of the philosopher Hans Reichenbach, into his economics. His philosophical commitments are clearly reflected in this empirical work on monetary economics, his monetarist analysis, and in his critical approach to econometrics, microfoundations, and the New Classical macroeconomics.
Keywords: B2; B3; B4; 330; Karl Brunner; philosophy of economics; philosophy of science; logical empiricism; econometrics; microfoundations; the New Classical macroeconomics